Attitude towards adherence to long term therapy - Sarkar, Paramita; Bagchi, Abantika; Sarkar, Dipanwita; Rajesh K Dalal; Chakrabarty, Swarnanka; Basu, Rivu (Indian Journal of Community Health, 2020)
Background: Chronic disease is a common public health problem worldwide. Adherence to long-term treatment is a key determinant of therapeutic success in patients with chronic diseases. Aim & Objective: The purpose of the study was to know the people’s attitude towards intake of drug, medication adherence and their relationship with socio demographic profile. Settings and Design: Data were collected from 729 individuals chronic disease sufferers chosen randomly from all 81 villages of Amdanga Block West Bengal through a household-based survey in a cross- sectional design. Methods and Material: A pre designed, pre tested, semi structured schedule containing socio-demographic profile and attitude among the respondents regarding adherence to long-term treatment. Statistical analysis used: To compare Attitude scores among different groups, median (IQR) attitude score was calculated and compared with Mann-Whitney U test and Kruskal-Wallis test to know the level of significance of variables. p–value < 0.05 considered statistically significant. Results: Attitude towards long-term adherence to treatment to chronic diseases were significantly associated to caste (p=0.043), education (p=0.001) and occupation (p=0.001) of the study subject. Conclusions: Attitude towards long-term adherence to treatment to chronic diseases were significantly associated to caste, education and occupation.